Religion, ethnicity and contested nationhood in the former Ottoman space (Leiden ; Boston)
x, 293 sayfa
Keywords: “There has been a growing interest in recent years in reviewing the continued impact of the Ottoman empire even long after its demise at the end of the First World War. The wars in former Yugoslavia, following hot on the civil war in Lebanon, were reminders that the settlements of 1918-22 were not final. While many of the successor states to the Ottoman empire, in east and west, had been built on forms of nationalist ideology and rhetoric opposed to the empire, a newer trend among historians has been to look at these histories as Ottoman provincial history. The present volume is an attempt to bring some of those histories from across the former Ottoman space together. They cover from parts of former Yugoslavia, Bulgaria and Greece to Lebanon, including Turkey itself, providing rich material for comparing regions which normally are not compared“ --